COMMON FOREST TREE DISEASES IN THAILAND - Chalermpongse, Aniwat (วารสารวนศาสตร์ไทย, 2022)
Forest Pathology research in Thailand was initiated by the Forest Pest Control Branch. Division of Silviculture, Royal Forest Department, Bangkok. Thailand in 1977. At present, very few researchers are working in this specialized field. Their objectives are to carry out research in Forest Pathology and Microbiology in different forest ecosystems of Thailand. This paper summarizes current potentially dangerous forest tree diseases identified and reported in Thailand. Some control measures are also recommended on the basis of laboratory and field practices. Future research should focus on the biology and ecology of serious diseases to provide data for control management in the field.